The Life Changer: Social Workers in Rehabilitation Facilities for Child in Conflict with the Law - Mark Erana Patalinghug (Otoritas : Jurnal Ilmu Pemerintahan, 2021)
Delinquent minors are offered special services intended to prevent them from entering the juvenile justice system. Through productive activities, delinquents are trained to acquire socially acceptable behavior with the help of social workers. This phenomenological study explored the social workers' experiences in handling juvenile cases. The study focused on 10 social workers from rehabilitation facilities of children in conflict with the law in the Zamboanga Peninsula Region, Philippines. The result of the study revealed that working with the juvenile's case, social workers have encountered positive and negative experiences. The study leads to the challenges and plight of social workers in their day-to-day activity in juvenile case management. As for how the participants coped with the challenges, they have been mentored and adjusted very well like their work. They also managed their challenges by viewing them as advocacy and service to humanity through altruistic activities.